STRATEGI BERTAHAN HIDUP RUMAH TANGGA PENJUAL LEMANG TAPAI DI JALAN JENDERAL SUDIRMAN PEKANBARU - Yulius Usman; Yusmar Yusuf (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The new Pekanbaru city as one of the fastgrowing cities in the constructions of the quick development made exiciting communities that could compete in the finding sustenance one of the jobs was selling lemang tapai .Works as a Lemang Tapai Selling with an income that barely is hard to imagine with such conditions how they can afford welfare of the family, educate their children, and live with the necessities of life are now all hyper-expensive, the theory used is edi sunarto, about survival strategies, and research methods used are a qualitative approach with in-depth interviews.The results showed that there are three strategies used to survive a gold prospector, namely: strategy of active, passive strategy and network strategy. Active strategy carried a Lemang Tapai Selling is to find another job, the family members to come to work and optimize available resources. Passive strategy carried a Lemang Tapai Selling that is by adopting a frugal life. Network strategy which carried lemang tapai selling are asked for help from family or neighbor. Keywords :Strategy Active, Passive Strategy, Network Strategy.